Structural and Morphological Characterization of MEH-PPV Nanocomposite Doped with FeCl3 - M. Jabbar, Noor; M- A. Hussein, Mustafa (Iraqi Journal of Physics, 2022)
Poly [2-methoxy-5-(2-ethylhexyloxy)-1, 4-phenylenevinyl] (MEH-PPV) thin films were created in this study using both spin coating and drop casting processes. MEH-PPV thin films generated by Ferric Chloride (FeCl3) doping (0.03, 0.06, 0.09, and 0.12 wt%) were studied for some physical features using Fourier-Transform Infrared Spectroscopy (FTIR), Field Emission Scanning Electron Microscopy (FE-SEM), and Energy Dispersive X-ray Spectroscopy (EDX). An FTIR test showed that there was no chemical reaction that occurred between Ferric Chloride (FeCl3) and MEH-PPV, but rather a physical one, that is, an organic material composite occurred. As for FE-SEM, the pure sample MEH-PPV formed uniformly, but when FeCl3 was added by weight, we have different circles that indicate the formation of adsorption energy and that the highest adsorption energy appears at MEH-PPV/FeCl3 (0.06%), as well as EDX, which indicates the absence of undesirable elements and indicates the presence of small peaks for iron (Fe) and chlorine (Cl). Peaks of carbon(C) and oxygen (O) types indicate the presence of the chemical elements of MEH-PPV.